Toilets, toasters & telephones : the how and why of everyday objects / Susan Goldman Rubin ; illustrated with photographs and with illustrations by Elsa Warnick. - Rubin, Susan Goldman (Browndeer Press, 1998)
Summary: Discusses the evolution of industrial design and the invention of a varibcy of household appliances